IMPLEMENTASI CORPORATE SOCIAL RESPONSIBILITY DALAM MENINGKATKAN CITRA PERUSAHAAN (Studi Pada BJB Syariah Cabang Cirebon): Implementasi CSR - Hamiid, Sharyan; Amir, Amir; Bakhri, Syaeful (FAKULTAS EKONOMI DAN BISNIS ISLAM, 2024)
Abstract Implementing Corporate Social Responsibility in a company can improve a good and strong image that the company needs for long-term business profits. The aim of this research is to analyze CSR implementation in improving the image of Bank BJB Syariah Cirebon Branch. This research was conducted using qualitative methods to look at CSR programs, while the tool for measuring CSR Implementation in Improving Company Image uses SWOT analysis which can analyze strategic plans for implementing CSR. The results of this research show that Bank BJB Syariah Cirebon Branch is able to provide great benefits so that it can improve a good image for the company. This can be seen from the fulfillment of the indicators for forming the company's image in the form of planning, availability and implementation. Keywords: CSR, Company Image, BJB Syariah Cirebon Branch.